First record and one new species of Cerconychia Klapálek, 1913 (Plecoptera: Styloperlidae) from Shaanxi Province of the Northwest China - Mo, Raorao; Yao, Gang; Wang, Guoquan; Li, Weihai (Zootaxa, 2019)
The family Styloperlidae is reported from Shaanxi Province of northwestern China for the first time with the description of a new species of the genus Cerconychia, C. trilobata sp. nov. The relationships based on morphological characteristics of the new species and related species are discussed.